AICCRA Scaling Vision: Mali - Koichi Futakuchi; Dossou-Yovo, Elliott Ronald; Guindo, Samuel; Doumbia, Salif; Sidibec, Mahamoudou; Diarra, Ba Affoussata; Futakuchi, Kiochi (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
AICCRA-Mali scaling vision is to ensure that by 2030, 1,000,000 farmers, including 35% women use the CSA and CIS interventions developed, validated, or scaled by the project to enhance the security of income, employment and food including nutrition in the face of climate change. The short-term objective is to enhance the yield income, food, and nutrition security of 250,000 farmers including 35% women in the face of climate variability and climate change by December 2023 by adopting innovative partnerships and inclusive business models to ensure sustainability.